NUTRACKER SYNDROME - Peneva, Elena; Jovanovska, Elizabeta Stojovska; Maksudova, Darinka Lapevska; Ilievski, Mitko; Dimitrovska, Maja Jakimovska; Dodevski, Ace (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
In the nutcracker anatomy, the aortomesenteric angle is more acute, which leads to a compression of the left renal vein between the aorta and the superior mesenteric artery. As a result, there is an impended outflow of the left renal vein in the inferior vena cava. This is termed as nutcracker syndrome.  Complex of clinical symptoms exists in the nutcracker syndrome (NS). Nutcracker phenomenon (NP) is the term used to describe an anatomic finding without any clinical symptoms. The aim of this case study was to show the use of a multiphase computed tomography as a diagnostic method of choice in dealing with cases of nutcracker anatomy in patients. We present four cases of patients who underwent computed tomography of the abdomen. Two of the cases were with anterior nutcracker syndrome, one case was with posterior nutcracker syndrome and one case with nutcracker phenomenon. Establishing of the exact diagnosis in these patients is difficult, because of the rarity and variety in symptoms. Existence of the clinical symptoms distinguishes whether the patient has NS or NP. Multiphase CT scan of the abdomen with additional reconstructions in maximum intensity projection (MIP), volume rendering (VR) and multiplanar reconstruction (MPR) as an imaging method is the method of choice in the diagnosis of NS and NP. Keywords : nutcracker syndrome, nutcracker phenomenon, computed tomography, anatomic variations https://doi.org/10.55302/JMS2142047p